Frequency Map Measurements at the TPS. (November 2019) - Chen, C H; Chiu, M S; Chen, J Y; Tseng, F H; Chen, B Y; Huang, B Y; Hsu, T W; Lin, W Y; Kuo, C C; Tsai, H J; Liu, Y C; Chou, P J
Abstract: The Taiwan Photon Source (TPS) has been operated now for several years since its successful commissioning in December 2014 and has achieved reliable routine operation up to 500 mA with more than 10 hrs beam lifetime. Dynamic aperture (DA) measurements and associated frequency map analyses (FMA) at the TPS reveal beam dynamics behavior with and without insertion devices. A preliminary study based on turn-by-turn beam position monitor (BPMs) is presented in this paper.